2022
DOI: 10.3346/jkms.2022.37.e31
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of 40 Patients Infected With the SARS-CoV-2 Omicron Variant in Korea

Abstract: Since severe acute respiratory syndrome-coronavirus-2 variant B.1.1.529 (omicron) was first reported to the World Health Organization on November 24, 2021, the cases of the omicron variant have been detected in more than 90 countries over the last month. We investigated the clinical and epidemiological characteristics of the first 40 patients with the omicron variant who had been isolated at the National Medical Center in South Korea during December 4–17, 2021. The median age of the patients was 39.5 years. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
99
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 5 publications
21
99
1
Order By: Relevance
“…Additionally, hospital admission was significantly lower in patients infected during omicron prevalence than in patients infected during delta prevalence. This supports previous findings from South Africa and South Korea, 4 , 5 , 6 , 7 which showed the omicron variant to be milder in terms of severity. Finally, the duration of acute symptoms was shorter during omicron prevalence than during delta prevalence, with the average presentation of omicron being 2 days shorter than that of delta.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, hospital admission was significantly lower in patients infected during omicron prevalence than in patients infected during delta prevalence. This supports previous findings from South Africa and South Korea, 4 , 5 , 6 , 7 which showed the omicron variant to be milder in terms of severity. Finally, the duration of acute symptoms was shorter during omicron prevalence than during delta prevalence, with the average presentation of omicron being 2 days shorter than that of delta.…”
Section: Discussionsupporting
confidence: 92%
“…2 Early reports suggested infection with omicron was less severe than with previous variants. 3 , 4 , 5 , 6 A small (n=40) South Korean study 4 described the clinical presentation of omicron cases; there were no severe cases. Hospital admission rates in South Africa for cases infected with this variant have been significantly lower than for previous waves, in which other variants of concern were dominant.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Furthermore, the patients suffer from the commonest symptoms including runny nose, headache, and fatigue. 27 , 28 Taken together, these results indicated that the Omicron variant resulted in mild symptoms and a lower rate of hospitalization and mortality, compared to the Delta variant.…”
Section: Epidemiology and Features Of The Omicron Variantmentioning
confidence: 81%
“…Pneumonia is the predominant symptom of COVID‐19 patients infected with other VOCs. However, analysis of clinical and epidemiological characteristics showed that only a small proportion of Omicron infections displayed lung infiltrations consistent with pneumonia on chest image, and the majority presented with symptoms more akin to an upper respiratory tract infection 28,29 . In vivo studies with hamsters also revealed that the Omicron variant was less likely to infect the lungs when compared with the Delta variant 30 .…”
Section: Epidemiology and Features Of The Omicron Variantmentioning
confidence: 99%
See 1 more Smart Citation